Post-mortem muscle proteome of crossbred bulls and steers: Relationships with carcass and meat quality - Santiago, Bismarck [UNESP]; Baldassini, Welder [UNESP]; Neto, Otávio Machado [UNESP]; Chardulo, Luis Artur [UNESP]; Torres, Rodrigo [UNESP]; Pereira, Guilherme [UNESP]; Curi, Rogério [UNESP]; Chiaratti, Marcos Roberto; Padilha, Pedro [UNESP]; Alessandroni, Laura; Gagaoua, Mohammed (Elsevier, 2023)
This study investigated the skeletal muscle proteome of crossbred bulls and steers with the aim of explaining the differences in carcass and meat quality traits. Therefore, 640 post-weaning Angus-Nellore calves were fed a high-energy diet for a period of 180 days. In the feedlot trial, comparisons of steers (n = 320) and bulls (n = 320) showed lower (P < 0.01) average daily gain (1.38 vs. 1.60 ± 0.05 kg/d), final body weight (547.4 vs. 585.1 ± 9.3 kg), which resulted in lower hot carcass weight (298.4 vs. 333.7 ± 7.7 kg) and ribeye area (68.6 vs. 81.0 ± 2.56 cm2). Steers had higher (P < 0.01) carcass fatness, meat color parameters (L*, a*, b*, chroma (C*), hue (h°)) and lower ultimate pH. Moreover, lower (P < 0.01) Warner-Bratzler shear force (WBSF) were observed in steers compared to bulls (WBSF = 3.68 vs. 4.97 ± 0.08 kg; and 3.19 vs. 4.08 ± 0.08 kg). The proteomic approach using two-dimensional electrophoresis, mass spectrometry and bioinformatics procedures revealed several differentially expressed proteins between steers and bulls (P < 0.05). Interconnected pathways and substantial changes were revealed in biological processes, molecular functions, and cellular components between the post-mortem muscle proteomes of the compared animals. Steers had increased (P < 0.05) abundance of proteins related to energy metabolism (CKM, ALDOA, and GAPDH), and bulls had greater abundance of proteins associated with catabolic (glycolysis) processes (PGM1); oxidative stress (HSP60, HSPA8 and GSTP1); and muscle structure and contraction (TNNI2 and TNNT3). The better carcass (fatness and marbling degree) and meat quality traits (tenderness and color parameters) of steers were associated with higher abundance of key proteins of energy metabolism and lower abundance of enzymes related to catabolic processes, oxidative stress, and proteins of muscle contraction Significance: Sexual condition of cattle is known to be an important factor affecting animal performances and growth as well as the carcass and meat quality traits. The investigation of skeletal muscle proteome help a better understanding of the origin of the differences in quality traits between bulls and steers. The inferior meat quality of bulls was found to be due to the greater expression of proteins associated with primary and catabolic processes, oxidative stress, and muscle contraction. Steers had greater expression of proteins, from which several are known biomarkers of beef quality (mainly tenderness).
Keywords: Beef tenderness; Feedlot, meat color, proteomics, biological mechanisms; Mass spectrometry; Meat quality; Proteome